Entrepreneurial Personality Dispositions and Coping with Stress - Konrad JANOWSKI (Communications of International Proceedings, 2021)
Background. Entrepreneurs experience elevated levels of psychological stress. However, ambiguous results exist on how efficiently they cope with it. It is hypothesized that people who choose the entrepreneur’s career may be predisposed to use more efficient strategies of coping with stress in comparison to non-entrepreneurs due to the association between entrepreneurial personality dispositions and coping behaviors. The objective of this study was to verify whether the levels of entrepreneurial personality dispositions are indeed related to the use of specific strategies and styles of coping with stress. Participants and Methods. A sample of 100 entrepreneurs was recruited and completed questionnaires measuring entrepreneurial dispositions (Entrepreneurial Dispositions Personality Inventory) and coping behaviors (Brief-Cope). Results. Adaptive coping strategies were positively, whereas maladaptive coping strategies – negatively correlated with a range of entrepreneurial dispositions. The subgroup of participants characterized by the active autonomous coping style revealed significantly higher levels of several entrepreneurial dispositions than the subgroups with active socially dependent and passive avoidance coping styles. Conclusions. Entrepreneurial personality dispositions are linked to more adaptive coping behaviors, therefore actual entrepreneurs (with higher entrepreneurial personality dispositions) may be more efficient at coping with stress.
Keywords: Entrepreneurial Personality; Coping Behavior; Stress